The Pengaruh Digital Marketing dan Lifestyle Terhadap Keputusan Pengguna Mobile Learning (Ruang Guru) di Industri 4.0 - Ida Nyoman Basmantra; Ni Wayan Widhiasthini; Ida Ayu Indah Purwita (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research aimed to determine the effect of Digital Marketing and Lifestyle on the decision of users of Mobile Learning (Ruang Guru) in industry 4.0. It was conducted in quantitative research design in which the data source was secondary data in the form of Ruang Guru user data. The data were collected through a questionnaire and analyzed by multiple linear regression with classic assumptions, namely Normality Test, Multicollinearity Test, Heteroskedasticity Test. Capital feasibility test was the coefficient of determination, F Test and t Test. Based on the result of the classic assumption test, it showed that Digital Marketing and Lifestyle had a positive and significant effect on the dependent variable of Mobile Learning user decision in Ruang Guru. By using a multiple regression analysis system, the research showed that Digital Marketing and Lifestyle partially influenced the decision of Mobile Learning users with the value of Digital Marketing variable ttest 11,973 > ttable 1,671 and ttest Lifestyle tcount 5,105 > ttable1,671. The result indicated the Digital Marketing and Lifestyle variables simultaneously had a positive effect on the decision of Mobile Learning users in the amount of 81,2% and 18,8% explained by other variables outside the research.